GENOME-WIDE ASSOCIATION STUDY OF GRAIN QUALITY TRAITS IN SPRING BARLEY COLLECTION GROWN IN KYZYLORDA REGION (Experimental biology, 2021)
Barley, among many other crops, has better resistance to harsh environmental conditions. Still, high temperature, drought, and soil salinity prevent the formation of high-quality grain, especially for the malting and brewing industry. In this study, spring barley accessions were tested in conditions of high-salinity soil of Kyzylorda region and analyzed for major grain quality traits, including protein, β-glucan, and starch contents, plumpness, grain hardness, and extractivity. Based on the results, the list of accessions optimal in the region for malting and the list for livestock feeding was made using the abovementioned traits. Genome-wide association study revealed 20 marker-trait(s) associations combined into 7 quantitative trait loci (QTLs). Three QTLs demonstrated pleiotropic effect affecting grain protein, β-glucan, and starch content and extractivity, two QTLs were identified for grain protein and starch content and extractivity, one QTL was for grain hardness index, and one QTL for plumpness. Identified pleiotropic QTLs were genetically mapped in the vicinity of known barley flowering genes. QTLs identified in the study, as well as promising accessions, can be integrated into the barley breeding process in stressed conditions of Kyzylorda region.